Manajemen Risiko Dana Tabarru' PT. Asuransi Jiwa Syariah Al Amin - Hifi Saniatusilma; Noven Suprayogi (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
The purpose of this study is to find out the risk management of tabarru' funds. As an institution that works to manage risk, islamic insurance has a duty to manage the tabarru’ funds. There is the possibility of a risk at tabarru’ fund. So, islamic insurance institution have a duty for risk management process of tabarru’ funds. This study uses a qualitative approach. Data research obtained by interview and documentation with the head and the deputy of Al Amin Surabaya branch. The results of this study, PT. Asuransi Jiwa Syariah Al Amin was execute the risk management process implemented by the four stages. Risk identification through underwriting limit process; rank the risk based on impact and complexity of risk;control risks by self retention; and response to the risk through change of insurance rates, products diversification and sharing of risk with reinsurance.